2006
DOI: 10.1177/0307174x0603300404
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerisation of Propylene and Ethylene in Liquid Propylene in the Presence of a Homogeneous Isospecific Metallocene Catalytic System

Abstract: Polypropylene (PP) is one of the most important polymeric materials. At present, this plastic is second only to polyethylene in world volume of consumption [1]. Isotactic polypropylene (IPP) is used in the building industry, in the motor industry, in the aircraft industry, in agriculture, in the textiles industry, in medicine, and so on. There are now about 80 different grades of PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…[3,4,[7][8][9] The molar content of the comonomers was measured by NMR C 13 and IR-spectroscopy. Detailed description of the synthesis, X-ray analysis and DSC data, and mechanical characteristics of the neat PP and copolymers were published earlier.…”
Section: Experimental Partmentioning
confidence: 99%
See 3 more Smart Citations
“…[3,4,[7][8][9] The molar content of the comonomers was measured by NMR C 13 and IR-spectroscopy. Detailed description of the synthesis, X-ray analysis and DSC data, and mechanical characteristics of the neat PP and copolymers were published earlier.…”
Section: Experimental Partmentioning
confidence: 99%
“…Detailed description of the synthesis, X-ray analysis and DSC data, and mechanical characteristics of the neat PP and copolymers were published earlier. [3,4,[7][8][9] It was found that Young's modulus decreased while the elongation at break increased with growing the content of the incorporated monomer. [3,4,[7][8][9] This indicates that the copolymers become more plastic.…”
Section: Experimental Partmentioning
confidence: 99%
See 2 more Smart Citations
“…Variations in relative content of comonomers, catalyst type and synthesis conditions allow tuning materials properties, such as mechanical, thermophysical, optical, etc., in a predictable manner and on a wide range. For example, recently synthesized with homogeneous isospecific catalytic system copolymers of propylene with ethylene, 1‐hexene, and 4‐methyl‐1‐pentene3, 4 differ significantly in mechanical characteristics. Depending on the relative content of the comonomers, tensile behavior of these materials3, 4 varied from rigid and quite brittle for the homopolymer to pronounced elastic for the copolymers.…”
Section: Introductionmentioning
confidence: 99%